Evolusi Lingkungan Solear Kabupaten Tangerang: Dampak Pembangunan Stasiun KRL Tigaraksa 1993–2013 - Muslimah Azzahrah Hasibuan; Nina Witasari (Universitas Veteran Bangun Nusantara, 2026)
This environmental history research aims to analyze the spatial and demographic evolution of Solear District, Tangerang Regency, in response to the development initiative of the Tigaraksa KRL Station. The periodization covered is between 1993, marking the designation of Tigaraksa as the administrative center, and 2013, when the electrification and operation of the KRL at the station began. Specifically, this study examines how the construction of double tracks and railway electrification (intensively started since 2008) served as the main trigger for environmental changes in the Solear area. The findings indicate that the KRL infrastructure created a partial Transit Oriented Development (TOD) effect that was unplanned. The most significant change is seen in the accelerated land use conversion, where the dominant rice fields and vacant land in Solear in 1993 transformed into dense residential and commercial areas by 2013. The accessibility guaranteed by the KRL attracted urbanization flows and property investment, drastically increasing land economic value and changing Solear's landscape from an agricultural support area into an urban buffer zone dependent on Jakarta connectivity. The conclusion shows that transportation infrastructure, even at the development stage, has a rapid and profound impact on the environmental and spatial evolution of Solear.